2022
DOI: 10.17576/jkukm-2022-si5(2)-06
|View full text |Cite
|
Sign up to set email alerts
|

Kesedaran Pengurusan Sisa Botol Plastik di Kalangan Pelajar Kolej Vokasional di Malaysia

Abstract: The management of solid waste, particularly plastic bottle waste, is becoming increasingly important. The carelessness with which solid waste is managed will have a negative impact on human life. A study was conducted to assess the effectiveness of vocational college students in addressing the problem of discarded plastic bottles. The study was conducted online, with vocational students in Malaysia receiving a link containing animation videos and open-ended questions. The students are then asked for their thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study among students of Politeknik Tuanku Sultanah Bahiyah, Kulim, found very satisfactory levels of knowledge and practice in recycling (Khalil et al 2023). Vocational college students are aware of the problems of plastic bottles, suggest solutions, and link waste management's importance to environmental conservation and public health (Mohamada et al 2022). However, recycling campaigns at an IPG campus started slowly but improved with modifications (Wai et al 2022).…”
Section: Recycling (Recycle)mentioning
confidence: 99%
“…A study among students of Politeknik Tuanku Sultanah Bahiyah, Kulim, found very satisfactory levels of knowledge and practice in recycling (Khalil et al 2023). Vocational college students are aware of the problems of plastic bottles, suggest solutions, and link waste management's importance to environmental conservation and public health (Mohamada et al 2022). However, recycling campaigns at an IPG campus started slowly but improved with modifications (Wai et al 2022).…”
Section: Recycling (Recycle)mentioning
confidence: 99%